The Sealing Ability of Resilon and Gutta-Percha in Severely Curved Root Canals: An In Vitro Study - Rouhani, Armita (Tehran University of Medical Sciences, 2013)
OBJECTIVE: The aim of this study was to compare the apical seal of curved canals obturated with Resilon/Epiphany with gutta-percha/AH Plus. MATERIALS AND METHODS: Thirty-four extracted human mandibular molars with 25–40 degree canal curvature of the mesial root were selected for this study. After preparation, the mesiobuccal canals were obturated with gutta-percha and AH- Plus sealer (group G) or Resilon and Epiphany sealer (group R). Four specimens served as control. Microleakage was evaluated after passing 3 and 30 days using the fluid filtration technique. The data were analyzed statistically using parametric tests. RESULTS: In the 3-day evaluation, the mean microleakage in group R was significantly less than in group G (P< 0.05). After 30 days, there was no significant difference between the two groups (P> 0.05). In group G, the leakage values at the end of 30 days were significantly less than values at the end of 3 days. Although in group R the mean leakage decreased after 30 days, this reduction was not statistically significant. CONCLUSION: Resilon/Epiphany provided a better seal than gutta-percha/AH-Plus in severely curved root canals immediately after obturation, although with the passage of time, Resilon/Epiphany was equivalent to gutta-percha/AH Plus in sealing properties.